Phase III Randomized Study of SB5, an Adalimumab Biosimilar, Versus Reference Adalimumab in Patients With Moderate‐to‐Severe Rheumatoid Arthritis. Issue 1 (21st November 2017) - Weinblatt, Michael E.; Baranauskaite, Asta; Niebrzydowski, Jaroslaw; Dokoupilova, Eva; Zielinska, Agnieszka; Jaworski, Janusz; Racewicz, Artur; Pileckyte, Margarita; Jedrychowicz‐Rosiak, Krystyna; Cheong, Soo Yeon; Ghil, Jeehoon
Abstract : Objective: SB5 is a biosimilar agent for adalimumab (ADA). The aim of this study was to evaluate the efficacy, pharmacokinetics (PK), safety, and immunogenicity of SB5 in comparison with reference ADA in patients with rheumatoid arthritis (RA). Methods: In this phase III, randomized, double‐blind, parallel‐group study, patients with moderately to severely active RA despite treatment with methotrexate were randomized 1:1 to receive SB5 or reference ADA at a dosage of 40 mg subcutaneously every other week. The primary efficacy end point was the response rate based on the American College of Rheumatology 20% improvement criteria (ACR20) at week 24 in the per‐protocol set (completer analysis). Additional end points included efficacy, PK, safety, and immunogenicity assessments. Results: Of the 544 patients randomized to receive a study drug, the full analysis set comprised 542 patients (269 in the SB5 group, 273 in the reference ADA group) and the per‐protocol set comprised 476 patients (239 receiving SB5, 237 receiving reference ADA). The ACR20 response rate at week 24 in the per‐protocol set was equivalent between those receiving SB5 and those receiving reference ADA (72.4% and 72.2%, respectively); the difference in the ACR20 response rate (0.1%, [95% confidence interval −7.83%, 8.13%]) was within the predefined equivalence margin (±15%). Similar results were seen in the full analysis set (missing data being considered a nonresponse). The SB5 and reference ADA treatment groups were comparable across other end points, including the ACR 50% and ACR 70% improvement response rates, Disease Activity Score in 28 joints based on the erythrocyte sedimentation rate, PK data, incidence of treatment‐emergent adverse events, and the antidrug antibody response. Subgroup analyses showed that the efficacy and safety of SB5 and reference ADA were comparable regardless of antidrug antibody status. Conclusion: The ACR20 response rate at week 24 was equivalent between patients treated with the biosimilar agent SB5 and those treated with reference ADA. SB5 and reference ADA were both well tolerated, with comparable safety profiles, in patients with RA.